DUKU PEEL INNOVATION: EFFORTS TO IMPROVE CREATIVE HEALTHPRENEURS THROUGH THE DEVELOPMENT OF PLANT-BASED INSECTICIDES - Tengku Arief Buana Perkasa; Huntari Harahap; Hafizah Hafizah; Denok Tri Hardiningsih; I Made Dwi Mertha Adnyana; Miftahurrahma Miftahurrahma (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
Duku peel is an underutilized agricultural byproduct in Talang Duku Village, a major center of duku production, and is commonly discarded as waste. The community’s heavy reliance on synthetic chemical insecticides presents environmental and health risks, compounded by limited knowledge regarding the processing of agricultural waste into value-added products. This community service program aimed to empower the “A. Khalik Duku Plantation” Farmers Group by converting duku peel waste into a high-value plant-based insecticide in the form of aromatherapy candles, thereby fostering a new generation of creative healthpreneurs. The program applied a participatory community empowerment approach through education, hands-on training, and continuous mentoring. The stages included needs assessment, production and business management training, and evaluation using pre-test and post-test data analyzed with the Wilcoxon and Chi-Square tests. The results showed a significant improvement in participants’ knowledge (P < 0.001), with the median score increasing from 70% to 80% and the number of participants achieving the ≥80% competency threshold rising from 13 to 49. Furthermore, the program successfully facilitated the production of insect-repellent aromatherapy candles and the establishment of the “KUB Duku Lestari” Joint Business Group, which sold more than 50 units within the first three months. In conclusion, this program effectively transformed agricultural waste into a valuable product, promoted sustainable entrepreneurship, and contributed to improving community welfare. It is recommended that the business group standardize product packaging to enhance market competitiveness and that future studies focus on optimizing extraction techniques to improve product efficacy.